2010
DOI: 10.1016/j.molcel.2010.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Major Role of O-Phosphoseryl-tRNA Kinase in the UGA-Specific Encoding of Selenocysteine

Abstract: The 21(st) amino acid, selenocysteine (Sec), is assigned to the codon UGA and is biosynthesized on the selenocysteine-specific tRNA (tRNA(Sec)) with the corresponding anticodon. In archaea/eukarya, tRNA(Sec) is ligated with serine by seryl-tRNA synthetase (SerRS), the seryl moiety is phosphorylated by O-phosphoseryl-tRNA kinase (PSTK), and the phosphate group is replaced with selenol by Sep-tRNA:Sec-tRNA synthase. PSTK selectively phosphorylates seryl-tRNA(Sec), while SerRS serylates both tRNA(Ser) and tRNA(Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 38 publications
(58 reference statements)
5
66
0
Order By: Relevance
“…To test for possible "overfitting" of that kind, we examined the noncanonical amino acids selenocysteine (Sec) and pyrrolysine (Pyl). Both amino acids are incorporated into proteins by codon dependent translation, co-opting either a stop codon (Pyl; UAG 31,32 ) or a redundant and rarely used serine codon (Sec; AGU [33][34][35] ) to enlarge the genetic code. These noncanonical amino acids involve changes in both the cognate tRNAs and the enzymes that recognize them.…”
Section: Cross-validationmentioning
confidence: 99%
“…To test for possible "overfitting" of that kind, we examined the noncanonical amino acids selenocysteine (Sec) and pyrrolysine (Pyl). Both amino acids are incorporated into proteins by codon dependent translation, co-opting either a stop codon (Pyl; UAG 31,32 ) or a redundant and rarely used serine codon (Sec; AGU [33][34][35] ) to enlarge the genetic code. These noncanonical amino acids involve changes in both the cognate tRNAs and the enzymes that recognize them.…”
Section: Cross-validationmentioning
confidence: 99%
“…The absence of these interactions makes the tRNA Sec conformation more flexible compared with that of other cytosolic tRNAs. The existence of such flexibility has already been noticed when the available x-ray conformations of the tRNA Sec were compared with each other (5,8). The flexibility provided by the absence of standard tertiary interactions seems to be essential for the tRNA Sec function.…”
Section: Discussionmentioning
confidence: 81%
“…However, it remains unclear how such an extension of the D-stem can be beneficial for the function of the tRNA Sec . In the archaeal and eukaryotic tRNAs Sec , the long D-stem may be important for the phosphorylation of the seryl moiety by O-phosphoseryl-tRNA kinase, an intermediate step required for the successful delivery of the amino acid selenocysteine (7,8). However, in bacteria, this reaction does not exist (9,10), and yet the D-stem of all bacterial tRNA Sec contains 6 base pairs.…”
mentioning
confidence: 99%
“…The length and secondary structure of the D-loop, but not its sequence composition, are the major components by which archaea and human PSTKs discriminate between tRNA Sec and tRNA Ser [22]. A mutated human tRNA Sec with a fourbase-pair D-loop showed decreased PSTK phosphorylation when compared with the wild type with a six-base-pair Dloop [22], and recent data demonstrated that identification of tRNA Sec in archaea is dependent on the D-loop structure [23]. Moreover, the Kinetoplastidae tRNA Sec has a 7/5 structure in the acceptor-T C stem, with seven nucleotides in the acceptor stem and five nucleotides in the T C stem, while the human [24] and the archaea [25] tRNA Sec have a 9/4 structure.…”
Section: Specific Characteristics Of Kinetoplas-tid Selenocysteine Bimentioning
confidence: 99%